Сопротивление материалов: учебное пособие - Хохлов В. А. Виктор Александрович; Цукублина К. Н. Капитолина Николаевна; Куприянов Н. А. Николай Амвросьевич; Логвинова Н. А. Наталья Александровна (Томск, Изд-во ТПУ, 2011)
Заглавие с титульного экрана